Students' conceptual and procedural understanding of conic sections through online guided discovery learning - Papa, Rejean Mosuela (Animo Repository, 2022)
Students’ conceptual and procedural understanding of Mathematics are important aspects in ensuring the achievement of math literacy, especially amid the changes in the educational system due to the COVID-19 pandemic. This study explored on incorporating the Guided Discovery Learning (GDL) approach in the teaching conic sections in mathematics. A total of 120 grade 11 senior high school students from one public school in Metro Manila who were taking Pre-Calculus subject during the 1st quarter of School Year 2020-2021 participated in this study. A prerequisite skills test was administered in order to know the level of students’ prior knowledge necessary for learning conic sections. Students were involved in five sessions each of asynchronous and synchronous classes incorporated with GDL approach. The researcher utilized video lessons and worksheets for students’ performance in a GDL setup. Students’ visualization skills of conic sections using GeoGebra applet was also looked into. After the intervention, concept tests were administered to determine students’ conceptual and procedural understanding of conic sections through GDL. Using mixed methods research design, the data were analyzed using descriptive statistics, thematic analysis, and qualitative descriptions of solutions. Also, Spearman Rank Correlation was used in order to determine if the prerequisite mathematical skills of the students are related to their conceptual understanding of conic sections. Results of the study showed that knowing the level of students’ prerequisite skills and knowledge before proceeding to learning conic sections helped both the students and the teacher. Regarding visualization skills, it was observed that there were different and various ways on how students visualize conic sections using GeoGebra applet. In this study, it was categorized according to levels of success – analytical, specific, limited/deficient, and misconceived visualization. Teaching conic sections through GDL has helped students discover concepts on conic sections on their own, with peers, and with the teacher’s guidance. The study also revealed that among the aspects of conceptual understanding, students found general principle knowledge easier to understand than knowledge of principles underlying procedures. It was also revealed that the prerequisite skills and knowledge of students are associated with their conceptual understanding of conic sections. The findings suggest the importance of conducting a recall of prior knowledge before introducing a new lesson. Also, the Guided Discovery Learning approach in teaching supports forming and developing students’ conceptual understanding of conic sections.